Piggies - Wood, Audrey (San Diego : Voyager Books/Harcourt Brace & Company, 1991)
Ten little piggies dance on a young child's fingers and toes before finally going to sleep.
Keywords: Bedtime-Fiction; Games-Fiction; Pigs-Fiction